Communications to the Editor—Tempus Fidgets: The Reference Business - Ehrenberg, A. S. C. (Management Science, 1971)
In their comments on “Models of Fact”, Charnes, Cooper, DeVoe and Learner [Charnes, A., W. W. Cooper, J. K. DeVoe, D. B. Learner. 1971. Models of fact and laws of behaviour. Management Sci. 17 367–369.] state that they will avoid a direct reply to my claims and criticisms. In following this precedent, I remark briefly on the pertinent use of references, an important matter in our work.